The law of rights of light - Barnes, Michael, 1943- (Oxford ; Portland, Oregon : Hart Publishing Ltd, 2015)
The book provides the authoritative statement on the current law on rights of light in England and Wales. The protection of the access of natural light to properties has been a part of our property law for centuries but in recent years has come into particular prominence. This is due to a number of reasons including the existence of easements of light being regarded as an inhibition on new development and the unsatisfactory nature of parts of the law on this subject. This has given rise to two reports in recent years by the Law Commission (one on easements generally in 2011 and one on rights of light specifically in 2014), both containing major proposals for law reform. The purpose of this legal textbook is to explain the law as clearly as possible. In practice rights of light issues and disputes involve technical subjects and inevitably answers to these questions require the expertise of technical experts such as light surveyors. An attempt is made in the book to explain from a non-technical point of view the way in which measurements and calculations are carried out in this area. It is therefore hoped that the book will be of use to lawyers as well as to landowners who may not always understand these technical subjects and to surveyors who may not always be familiar with the legal concepts and difficulties involved in the area of the law of rights of light
Introduction -- The legal nature of the right of light -- Content of the right of light -- Acquisition of rights by deed -- Acquisition of rights of light by prescription -- The measurement of light -- Remedies -- Extinguishment and overriding of rights of light -- The Rights of Light Act 1959 -- Town planning -- Registration and transfer of easements of light -- Reform -- Appendix 1: Prescription Act 1832 -- Appendix 2: Rights of Light Act 1959.
Includes bibliographical references and index.
Also issued in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Solar access rights -- England